2016
DOI: 10.3389/fphar.2016.00465
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative and Apoptosis-Inducing Effect of Theabrownin against Non-small Cell Lung Adenocarcinoma A549 Cells

Abstract: With the highest cancer incidence rate, lung cancer, especially non-small cell lung cancer (NSCLC), is the leading cause of cancer death in the world. Tea (leaves of Camellia sinensis) has been widely used as a traditional beverage beneficial to human health, including anti-NSCLC activity. Theabrownin (TB) is one major kind of tea pigment responsible for the beneficial effects of tea liquor. However, its effect on NSCLC is unknown. The aim of the present study was to evaluate anti-proliferative and apoptosis-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Apart from polyphenols, TB attracts increasing attention in recent years due to its bioactivities and therapeutic potential . In our previous studies, TB exerted strong pro‐apoptotic effects against non‐small cell lung cancer via the p53 signalling pathway . Using xenograft model and osteosarcoma cells, this study investigated the anti‐OS effects and molecular mechanism of TB.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Apart from polyphenols, TB attracts increasing attention in recent years due to its bioactivities and therapeutic potential . In our previous studies, TB exerted strong pro‐apoptotic effects against non‐small cell lung cancer via the p53 signalling pathway . Using xenograft model and osteosarcoma cells, this study investigated the anti‐OS effects and molecular mechanism of TB.…”
Section: Discussionmentioning
confidence: 96%
“…TB comprises of a family of macromolecules transformed from polyphenols, and is considered superior to TF or TR in physicochemical and medicinal properties. Previously, we reported that TB possessed strong pro‐apoptotic and cell cycle arresting effects on human carcinoma cells, making it a promising candidate for cancer therapy . To determine its anti‐OS effect, this study employed U2OS cells and performed in vivo and in vitro assays.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have reported that DNA damage induction was associated with P53 pathway-mediated pro-apoptotic mechanism of theabrownin ( Wu et al, 2016 ; Jin et al, 2018 ). However, although both TF and theabrownin activated P53 pathway and induced tumor cell apoptosis, we did not find DNA damage induction with TF treatment in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Several research groups have indicated that cell growth encourages cell survival and decreases the opportunity for cell death or apoptosis (47)(48)(49)(50)(51)(52). Based on differences in G1 and S between HCC 1806 and L133 TK1-/-, we propose that TK1 may be influencing cell cycle transitions, specifically S to G2.…”
Section: Exploring Factors In Invasion Apoptosis and Progressionmentioning
confidence: 93%